SETTLEMENT OF APARTMENT ARREARS ON A NON-LITIGATION BASIS BETWEEN MRS. MP AND PT. ELITE ON CONSUMER PROTECTION LAWS - Gunawan, Indra (Transnational Business Law Journal, 2021)
Consumer protection is a consequence of the force of law in meeting the interests of consumers. This requires a balance between the quality of service so that creditors/banks improve the quality of service in a fair (honest) manner to inform in detail about advertising and other services. to the ever-changing demands of this era of globalization. The legal force in information is a means of consumer protection in an agreement that is mutually binding between rights and obligations. Consumer protection law as the basis for the settlement of peace underhand on the heading "Settlement of Apartment Arrears in Non-litigation Between Mrs. Mut Pen and PT. ELITEE Related to Consumer Protection Act", is the title that the author gives in this Thesis. With the negotiations, the parties to the dispute where the case is a settlement are willing to continue the process of the rights and obligations of the parties to the dispute under mutually beneficial conditions, by waiving or relinquishing part of their rights in reaching an agreement on certain rights based on the principle of reciprocity to the word agree and there is no element of coercion from the other party.